2022
DOI: 10.4314/ijbcs.v15i5.37
|View full text |Cite
|
Sign up to set email alerts
|

Niveau de contamination et risques sanitaires liés à la consommation des produits maraîchers à Korhogo, Côte d’Ivoire

Abstract: L’usage non maîtrisé des pesticides a des effets sur la qualité des denrées alimentaires et la santé de la population. L’objectif de cette étude était d’évaluer l’exposition chimique associée à la consommation des produits maraîchers du département de Korhogo. A cet effet, des résidus de pesticides ont été extraits des produits maraîchers (Allium cepa, Lactuca sativa, Capsicum sp, Solanum lycopersicum et Phaseolus lunatus) par la méthode QuEchERS et analysés par un chromatographe en phase gazeuse couplé à un s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Studies have revealed the presence of contaminants in fruits and vegetables, in particular pesticides. Pesticides are chemical or biological agents' chemical or biological agents capable of destroying pests or controlling their growth and reproduction their reproduction [13]. Pesticides have negative impacts on the health of operators and consumers of contaminated products [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed the presence of contaminants in fruits and vegetables, in particular pesticides. Pesticides are chemical or biological agents' chemical or biological agents capable of destroying pests or controlling their growth and reproduction their reproduction [13]. Pesticides have negative impacts on the health of operators and consumers of contaminated products [4].…”
Section: Introductionmentioning
confidence: 99%